Opportunities and Challenges for Molecular Understanding of Ciliopathies–The 100,000 Genomes Project - Wheway, Gabrielle; , Genomics England Research Consortium; Mitchison, Hannah M.; Ambrose, J. C.; Baple, E. L.; Bleda, M.; Boardman-Pretty, F.; Boissiere, J. M.; Boustred, C. R.; Caulfield, M. J.; Chan, G. C.; Craig, C. E. H.; et al. (Frontiers in Genetics, 2019)
Cilia are highly specialized cellular organelles that serve multiple functions in human development and health. Their central importance in the body is demonstrated by the occurrence of a diverse range of developmental disorders that arise from defects of cilia structure and function, caused by a range of different inherited mutations found in at least 150 different genes. Genetic analysis has rapidly advanced our understanding of the cell biological basis of ciliopathies over the past two decades, with more recent technological advances in genomics rapidly accelerating this progress. The 100,000 Genomes Project was launched in 2012 in the UK to improve diagnosis and future care for individuals affected by rare diseases like ciliopathies, through whole genome sequencing (WGS). In this review we discuss the potential promise and medical impact of WGS for ciliopathies and report on current progress of the 100,000 Genomes Project, reviewing the medical, technical and ethical challenges and opportunities that new, large scale initiatives such as this can offer.